Potential Role of the Inflammasome-Derived Inflammatory Cytokines in Pulmonary Fibrosis - Rupa Biswas; Melisa Bunderson-Schelvan; Andrij Holian (Pulmonary Medicine)
Pulmonary fibrosis is a progressive, disabling disease with mortality rates that appear to be increasing in the western population, including the USA. There are over 140 known causes of pulmonary fibrosis as well as many unknown causes. Treatment options for this disease are limited due to poor understanding of the molecular mechanisms of the disease progression. However, recent progress in inflammasome research has greatly contributed to our understanding of its role in inflammation and fibrosis development. The inflammasome is a multiprotein complex that is an important component of both the innate and adaptive immune systems. Activation of proinflammatory cytokines following inflammasome assembly, such as IL-1β and IL-18, has been associated with development of PF. In addition, components of the inflammasome complex itself, such as the adaptor protein ASC have been associated with PF development. Recent evidence suggesting that the fibrotic process can be reversed via blockade of pathways associated with inflammasome activity may provide hope for future drug strategies. In this paper we will give an introduction to pulmonary fibrosis and its known causes. In addition, we will discuss the importance of the inflammasome in the development of pulmonary fibrosis as well as discuss potential future treatment options.